The politics of the pill gender, framing, and policymaking in the battle over birth control - VanSickle-Ward, Rachel 1977- (Oxford University Press, 2019)
"The announcement of a Health and Human Services (HHS) rule requiring insurance providers to cover the costs of contraception as part of the Affordable Care Act sparked widespread political controversy. How did something that millions of American women use regularly become such a fraught political issue? In The Politics of the Pill, Rachel VanSickle-Ward and Kevin Wallsten explore how gender has shaped contemporary debates over contraception policy in the U.S. Within historical context, they examine the impact that women and perceptions of gender roles had on media coverage, public opinion, policy formation, and legal interpretations from the deliberation of the Affordable Care Act in 2009 to the more recent Supreme Court rulings in Burwell v. Hobby Lobby Stores, Inc. and Zubic v. Burwell. Their central argument is that representation matters: who had a voice significantly impacted policy attitudes, deliberation and outcomes. While women's participation in the debate over birth control was limited by a lack of gender parity across institutions, women nevertheless shaped policy making on birth control in myriad and interconnected ways. Combining detailed analyses of media coverage and legislative records with data from public opinion surveys, survey experiments, elite interviews, and congressional testimony, The Politics of the Pill tells a broader story of how gender matters in American politics." --
Keywords: Geschichte 1960-2020; Empfängnisverhütung; Gesundheitspolitik; Familienplanung; Politik; Gesundheitswesen; Ethik; Sozialpolitik; USA; Birth control / Government policy / United States; Birth control / Law and legislation / United States; Reproductive rights / Political aspects / United States; Birth control / Government policy; Birth control / Law and legislation; United States